The epidemic status and recommendations for prevention and control strategies of stroke in China - WANG Wenzhi (Guangxi Yike Daxue xuebao)
At present, the prevalence of stroke is still very severe, causing serious harm to society and many families. The overall incidence of new stroke cases is still increasing, and the overall prevalence continues to rise. Compared with 1990, the number of stroke patients per 100, 000 people increased by 11.5% in 2021. The weighted morbidity and mortality in Northeast China were the highest, at 365.2 per 100, 000 and 158.5 per 100, 000, respectively. It is predicted that the prevalence and incidence of stroke in China will continue to rise with the continuous rise of several major risk factors such as hypertension, diabetes and dyslipidemia, as well as the accelerated aging of the population. Therefore, the reasonable recommendations for prevention and control strategies include: focusing on prevention, strengthening health education and promotion activities; carrying out community-based prevention and treatment of stroke population; formulating stroke prevention and control measures based on local conditions.